Arthritis as an initial presentation of malignancy: two case reports - Sachdev, Benjamin Manjit Singh; Sharifah Aishah, Wan; Cheong, Yaw Kiet; Chuah, Seow Lin; Teh, Cheng Lay; Ahmad Tirmizi, Jobli (BMC, 2021)
Abstract Background: Arthritis is rarely reported as a paraneoplastic manifestation of occult malignancy. We report herein two cases of paraneoplastic arthritis due to occult malignancy. Case 1: The patient was a 65-year-old woman of asian descent who was a former smoker with a history of spine surgery performed for L4/L5 degenerative disc disease. She presented with a 1-month history of oligoarthritis afecting both ankle joints and early morning stifness of about 3 hours. Laboratory tests were positive for antinuclear antibody at a titer of 1:320 (speckled) but negative for rheumatoid factor. She was treated for seronegative spondyloarthritis and started on prednisolone without much improvement. A routine chest radiograph incidentally revealed a right lung mass which was found to be adenocarcinoma of the lung. She was treated with geftinib and her arthritis resolved. Case 2: The patient was a 64-year-old woman of asign descent, nonsmoker, who presented with a chief complaint of asymmetrical polyarthritis involving her right wrist, second and third metacarpophalangeal joints, and ifrst to fifth proximal interphalangeal joints. She was treated for seronegative rheumatoid arthritis (RA) and started on sulfasalazine, with poor clinical response. Six months later, she developed abdominal pain which was diagnosed as ovarian carcinoma by laparotomy. Her arthritis resolved following treatment of her malignancy with chemotherapy. Conclusion: In summary, paraneoplastic arthritis usually presents in an atypical manner and responds poorly to disease-modifying antirheumatic drugs. Accordingly, we recommend screening for occult malignancy in patients presenting with atypical arthritis..